IMPLEMENTASI GAP ANALISIS DARI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) PADA KABUPATEN BENER MERIAH - ima dwitawati (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study presents a gap analysis of the implementation of Electronic-Based Government System (SPBE) in Bener Meriah Regency in 2021. The Gap Analysis was compiled based on the secondary data collection process in the form of the maturity level of the SPBE in Bener Meriah Regency which consists of the domains of policy, governance, management and SPBE services. The result of this research is a gap analysis which consists of a description of the area being analyzed, identification of the specific parts to be improved from the SPBE, the target achievement (desired state), the current state and an action plan based on the identification of the maturity level of SPBE process capabilities and technical functions